Trends in subjective income poverty rates in the European Union - Tomás Želinský; Martina Mysíková; Thesia I. Garner (Global Labor Organization (GLO), 2021)
When developing anti-poverty policies, policymakers need accurate data on the prevalence of poverty. In this paper, we focus on subjective poverty, a concept which has been largely neglected in the literature, though it remains a conceptually appealing way to define poverty. The primary goal of this study is to re-examine the concept of subjective poverty measurement and to estimate trends in subjective income poverty rates in the European Union. Our estimations are based on a Minimum Income Question using data from a representative survey, EU-SILC. We find robust empirical evidence of decreasing trends in subjective poverty in 16 of 28 EU countries. We conjecture that trends in subjective poverty may reflect changes in societies which are not captured by official poverty indicators, and our results thus enrich the existing data on general poverty trends in the EU.
Keywords: I31; I32; 330; Subjective poverty; Minimum Income Question; intersection approach; EU-SILC; European Union